Persaingan Industri Jasa Pendidikan Tinggi: Mengukur dan Meningkatkan Kualitas untuk Menciptakan Keunggulan Bersaing - Muhammad Johan Widikusyanto; Asmi Ayuning Hidayah (Sains: Jurnal Manajemen dan Bisnis, 2019)
This study is to measure, describe, and compare the level quality of university in Banten and determine strategies for improving overall quality and each university using importance performance analysis. The object in this study was eight hundred fifty students from eight universities in five regions of Banten. This research mehod use survey quesionnaires which analyzed statistik deskriptif, t-test, Chi-Square tests, Factor Analysis and Importance Performance Analysis.